2013
DOI: 10.1016/j.jceh.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-1β and Gene Polymorphisms with Liver Pathogenesis in Hepatitis B Virus Infection among Eastern Indian Population

Abstract: Background: Interleukin-1b (IL-1b) is an important member of the family of the proinflammatory cytokines that modulate outcome of hepatitis B virus (HBV) infection. Objectives: This study was designed to investigate the relationship between the polymorphic genotypes of the interleukin-1b (IL-1b) promoter region and the interleukin-1 receptor antagonist gene (IL-1RN) and disease outcome in HBV-infected individuals. Methods: DNA was extracted from 395 study subjects including HBV carriers with varying clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…A protective role was reported for the C/C genotype of the promoter region −511 and therefore less probability of the chronic hepatitis outcome in the Chinese population . In the Indian population, also the C/C genotype at this region was reported to be associated with a sustained response to HBV infection . However, in the Thai population, a higher frequency was reported of −511C/C genotype in the healthy controls in comparison to the patient with chronic hepatitis B .…”
Section: Discussionmentioning
confidence: 95%
“…A protective role was reported for the C/C genotype of the promoter region −511 and therefore less probability of the chronic hepatitis outcome in the Chinese population . In the Indian population, also the C/C genotype at this region was reported to be associated with a sustained response to HBV infection . However, in the Thai population, a higher frequency was reported of −511C/C genotype in the healthy controls in comparison to the patient with chronic hepatitis B .…”
Section: Discussionmentioning
confidence: 95%
“…Our study shows an increase in the buccal mucosal gene expressions of IL8 and IL1B in children that are carriers of any pneumococcal serotype in the nasal cavity at baseline even when adjusting for number of siblings as a potential risk factor for carriage of S. pneumoniae. Other studies have found a higher expression of IL8 and IL1B in serum in hepatitis B virus (HBV) infected patients [26][27][28] , while another study found mainly IL-10 to be expressed in HBV infected patients and HBV-vaccinated individuals 29 . Mucosal expression of IL8 and/or IL1B indicates activation of the mucosal immune system, which is expected in the presence of bacteria 30 .…”
Section: Discussionmentioning
confidence: 96%
“…Chronic HBV infection remains a serious global health problem [26,27]. It was reported that host genetic factors played an important role in the pathogenesis of HBV infection, and the polymorphisms of cytokine genes were strongly associated with the susceptibility to HBV infection in the general population [28,29]. ere is enough evidence that genetic variants of IFN-c signaling pathway genes play important roles in the HBV infection in adults [30][31][32].…”
Section: Discussionmentioning
confidence: 99%